Generational diversity among postgraduate doctors in training in the NHS: protocol for a qualitative study - Jane Thurlow; Louise J Hardy; Ian Higginson; Patricia Schofield; Matthew Alexander Boissaud-Cooke; Swetha Yatham (BMJ Open)
Introduction The concept of generations and generational diversity in the workplace is a widely discussed phenomenon in popular culture, organisational articles and research studies. A number of non-medical and medical organisations have attempted to identify generational differences among their workforces and devise solutions to overcome this. The impact of generational differences among the medical workforce, specifically postgraduate doctors-in-training (PGDiTs), in the National Health Service (NHS) has not been studied.Method and analysis This qualitative study will use a pragmatic study methodology with components of grounded theory and interpretative phenomenological analysis to explore and understand the concept, perceptions, experiences and sources of generational diversity among PGDiTs working in the NHS. Six focus groups will be conducted with PGDiTs recruited from a single acute NHS Trust. Participants will be stratified according to their generation (ie, Generation X, Y or Z). Two focus groups will be conducted for each generation. If insufficient participants are recruited for a focus group, then one-to-one interviews will be offered. The data from the focus groups and one-to-one interviews will be analysed using an inductive thematic analysis method using NVivo software.Ethics and dissemination This study has received approval from the Health Research Authority and Care Research Wales (Reference: 24/HRA/0770). Ethics committee approval is not required as the study involves NHS staff as research participants. The findings from this study will report a number of higher level themes reflecting the views and experiences of the research participants. The findings will be disseminated via academic conferences and peer-reviewed publications.NCT06446297.